Hypoxia-Induced VISTA Promotes the Suppressive Function of Myeloid-Derived Suppressor Cells in the Tumor Microenvironment - Deng, Jie; Li, Jiannan; Sarde, Aurelien; Lines, J Louise; Lee, Yu-Chi; Qian, David C; Pechenick, Dov A; Manivanh, Richard; Le Mercier, Isabelle; Lowrey, Christopher H; Varn, Frederick S; Cheng, Chao; et al. (Cancer immunology research, 2019)
Tumor hypoxia is a negative prognostic factor that is implicated in oncogenic signal activation, immune escape, and resistance to treatment. Identifying the mechanistic role of hypoxia in immune escape and resistance to immune-checkpoint inhibitors may aid the identification of therapeutic targets. We and others have shown that V-domain Ig suppressor of T-cell activation (VISTA), a negative checkpoint regulator in the B7 family, is highly expressed in the tumor microenvironment in tumor models and primary human cancers. In this study, we show that and HIF1α activity are correlated in a cohort of colorectal cancer patients. High expression was associated with worse overall survival. We used the CT26 colon cancer model to investigate the regulation of VISTA by hypoxia. Compared with less hypoxic tumor regions or draining lymph nodes, regions of profound hypoxia in the tumor microenvironment were associated with increased VISTA expression on tumor-infiltrating myeloid-derived suppressor cells (MDSC). Using chromatin immunoprecipitation and genetic silencing, we show that hypoxia-inducible factor (HIF)-1α binding to a conserved hypoxia response element in the promoter upregulated VISTA on myeloid cells. Further, antibody targeting or genetic ablation of VISTA under hypoxia relieved MDSC-mediated T-cell suppression, revealing VISTA as a mediator of MDSC function. Collectively, these data suggest that targeting VISTA may mitigate the deleterious effects of hypoxia on antitumor immunity.